Essays in regional economics - Kain, John F.; Meyer, John Robert (Cambridge, Mass. : Harvard University Press, 1971)
This volume consist of six survey papers by Chinitz, Bolton, Borts, Miernyk, Engerman, and Milliman, prepared specifically for the Harvard regional economic seminar. Four of the remaining papers in the volume present findings of EDA sponsored research done as part of the PRUE program.
Includes bibliographical references and index.
rpm 24/01/2019
Loans
Keywords: Regional planning